26 Comparison of effects of DORIS remission and lupus low disease activity state (LLDAS) on disease outcomes in a multinational prospective study. (April 2019) - Morand, Eric; Golder, Vera; Kandane-Rathnayake, Rangi; Huq, Molla; Nim, Hieu; Louthrenoo, Worawit; Luo, Shue Fen; Lateef, Aisha; Sockalingam, Sargunan; Navarra, Sandra; Hamijoyo, Laniyati; Katsumata, Yasuhiro; et al.
Abstract : Background: The Definitions of Remission in SLE (DORIS) group has proposed multiple definitions of remission, but these are infrequently attained and have not previously been evaluated in relation to protection from damage accrual. In contrast, the Lupus Low Disease Activity State (LLDAS) is more attainable, and has been shown to be associated with improved patient outcomes. The objective of this study was to compare the attainability and effect of LLDAS and remission on outcomes in a prospective multicenter study. Methods: A prospective multinational cohort study was undertaken in 13 centres between 2013–2017. Time dependent Cox proportional hazards models were used to compare LLDAS and DORIS definitions of remission in terms of impact on disease flares and damage accrual. Results: 1735 SLE patients were recruited, and followed for (mean ±SD) 2.2±0.9 years. LLDAS was achieved in 6922 visits (54.6%). In contrast, remission was achieved in 1.1%–15.4% of visits. LLDAS attainment at any visit was associated with significantly reduced subsequent flare (HR 0.65, 95% CI 0.56–0.76, p<0.001) and damage accrual (HR 0.55, 95% CI 0.43–0.70, p<0.001). In contrast, only the least stringent remission definition was associated with reduced damage accrual (HR 0.58, 95% CI 0.39–0.88, p 0.01). Only remission definitions including serological remission were significantly associated with reduction in subsequent flares. Patients who spent 50% of their observed time in LLDAS had two-fold reduction in risk of damage accrual (HR 0.53, 95% CI 0.41–0.68, p<0.001), while only the least stringent remission definition, or the related definition excluding serology, were significantly protective against damage (HR 0.59, 95% CI 0.42–0.83, p 0.003; HR 0.69, 95% CI 0.48–0.99, p 0.05, respectively). Conclusions: LLDAS was markedly more attainable than any remission definition, whilst still conferring significant protection against flares and damage accrual. Only the least stringent remission definitions could be shown to be associated with significant reduction in damage accrual, likely reflecting a low frequency of remission attainment overall; and normal serology was required for protection from flare. LLDAS is a valid treatment target for SLE and is more achievable than remission. Funding Source(s): The Asia Pacific Lupus Collaboration receives project support grants from UCB, GlaxoSmithKline, Janssen, Bristo-Myers Squibb, and AstraZeneca.